SEEKING ADEQUATE COMPENCIES FOR THE FUTURE: The Digital Skills of Finnish Upper Secondary School Students - Meri-Tuulia Kaarakainen; Suvi-Sadetta Kaarakainen; Antero Kivinen (NTNU Norwegian University of Science and Technology, 2022)
Digital skills are a prerequisite today for working, studying, civic participation, and maintaining social relationships in our digitalised technical world. These skills are also important both as a general goal and an instrument for learning. This study briefly presents the aims that are related to digital skills of the Finnish curricula, and explores, using a large sample (N = 3,206) of Finnish upper secondary school students, these young people's digital skills and their distribution. The study provides new insights into the state of these skills and differences found in them and focuses on the relationship between these results and the students' present educational choices and future study/employment intentions. The actual variability of digital skills among upper secondary students is one of the main findings of the study. On the same educational level, it was found that digital skills vary enormously, particularly for students' current educational choices and their future intentions. Digital skills are also distinctly associated with age for 15 to 22-year-olds. At the same time, gender alone appears to have no prominent effect on the level or adeptness of upper secondary school students' digital skills.
<a href="https://www.researchgate.net/figure/Six-modules-basic-operations-office-tools-communication-and-networking-content_fig1_327644507" title="Figure 1: Six modules (basic operations, office tools, communication...">